PERAN PEMUDA MEMBANGUN DESA: PENGABDIAN TERHADAP REMAJA ISLAM WATUALANG - Hanifah Hikmawati (As-Sidanah, 2019)
Abstract: This article discusses the results of the village youth Watualang dedication engaged in the field ofreligion as an effort to counter radicalism and improve the quality through education. Islamic Youth Watualang(Riswa) formed on 16 September 2016 the village youth organizations who continue to make innovation andcreativity to uphold the values of peace, brotherhood and unity. The existence of this youth group as well ascontemporary teen mediator associations that give a new color on the style propaganda comfortable. To get to thebottom of what makes this group is born, then formulated some formulation of the problem in ease of discussionand analysis in this article. First, how is the phenomenon of radicalism and terrorism threaten the younggeneration in Indonesia ?. Second, how does the existence of the Islamic Youth Watualang in proselytizing toshield themselves from the dangers of radicalism and terrorism. The method used is descriptive qualitative bypresenting source data from the journal and the results of previous studies, as well as some documentation ofdevotion to Riswa. The results obtained in this devotion is actively carrying out routine readings Riswa Maulidurmessengers in Tadarus Poetry Night event (Matapu), smeinar-seminars, educational outbound, and some otherforms of propaganda.